MEMBENTUK KEPRIBADIAN ULUL ALBAB SEBAGAI ORIENTASI PENDIDIKAN ISLAM - Auffah Yumni (NIZHAMIYAH, 2018)
Ulul Albab is the one who always get closer to Allah by means of dhikr wherever and whenever he is. They are always plugged kalimatullah in his heart, in addition he wanted to use his intelligence to always think and analyze the creation of Allah. Basically the fact aim of Islamic education is directed to the achievement of targets related to the fact of the creation of man by Allah. From this perspective, the fact of the purpose of education is to develop awareness of Muslims fact Abdullah learners as always submissive and obedient to all the rules of Allah. Kata Kunci: Ulul Albab, Relevansi, Pendidikan Islam